Pengembangan Aplikasi Kasir Penjualan Parfum Menggunakan Microsoft Visual Studio dengan Integrasi Database MySQL dan XAMPP - Salsabila, Fairuz; Panggabean, Teresa; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
The development of the retail business is growing rapidly in today’s digital era, driven by advances in information technology that provide great opportunities to continue to innovate. Sales management is one of the important elements to ensure operations run smoothly, especially in the perfume sales business that requires proper data management. However, many small businesses still rely on manual record-keeping, which is prone to human error. As a solution to overcome these challenge, a simple computer-based cashier system is needed that is able to record automatically and maintain the availability of goods to be more accurate. This research develops a perfume sales cashier application with Microsoft Visual Studio with the support of MySQL and XAMPP as a database that provides convenience. Hopefully, the development of this application will be a practical solution that supports the sustainability of small businesses in the digital era.